Harare City Council vehicle licensing and impounding system - Mugobogobo, William (Midlands State University, 2018)
This document outlines the author’s practical experiences in a real-life, working environment, within the operational structures of Harare Municipality. It gives a brief background of the organization’s history, core business, current operations and future business activities of the City of Harare. The report then outlines the problem definition, research instruments, and significance of the study and justification. The document further details the planning, design and implementation phases of the project.